Modeling Equal Opportunity - Isabel V. Sawhill; Richard V. Reeves (RSF: The Russell Sage Foundation Journal of the Social Sciences, 2016)
We examine the themes of equal opportunity, intergenerational mobility, and inequality. We address the normative and definitional questions of selecting measures of mobility and summarize the current state of intergenerational mobility in the United States and abroad. We introduce a new microsimulation model, the Social Genome Model (SGM), which provides a framework for measuring success in each stage of the life cycle. We show how the SGM can be used not only to understand the pathways to the middle class, but also to simulate the impact of policy interventions on rates of mobility.